Beam steering of four dipoles antenna array using genetic algorithm - Abdul Malek, Norun; Seager, Rob; Flint, James (2014)
This paper demonstrates the capability of four dipoles antenna (two-dimensional array) to steer the beam to arbitrary direction. A combination of genetic algorithm and array analysis based on the Induced EMF method optimised the input excitation of each dipole to maximise the main lobe to any azimuth direction. The optimisation is performed using MATLAB software. The Induced EMF method incorporates the mutual coupling between dipoles giving more accurate results in comparison with pattern multiplication method. The results show that the beam steering of a phased array antenna in two dimensions may be achieved using a genetic algorithm.